Identifikasi bakteri pada saluran akar gigi dengan diagnosis periodontitis apikalis kronis (Identification of bacteria in dental root canal diagnosed with chronic apicalis periodontitis) - Yeyen Sutasmi; Nurhayati Natsir (Journal of Dentomaxillofacial Science, 2014)
Chronic apical periodontitis is one of common periapical diseases. Inflammation in the periapical tissue is caused bybacteria from the root canal necrotic. If the tooth is not treated, the infection can progress to periapical region causingchronic apical periodontitis. The variety of bacteria can be found in root canal with chronic apical periodontitis. Thisstudy aims to determine the type of bacteria in chronic apical periodontitis. Samples were obtained from fifteen patientswith teeth that have chronic apical periodontitis in the Department of Conservative Dentistry in Dental Hospital ofHasanuddin University. Bacteria collected from a sample specimen using paper points which were inserted into the rootcanal. Subsequent, bacterial specimens identified in the Medical Microbiology Laboratory of the Medical Faculty,Hasanuddin University. This study found seven different types of bacteria with varying percentages. Type of Grampositivefacultative anaerobic bacteria Streptococcus spp. is the most dominant bacteria found in the root canal withchronic apical periodontitis. This study concluded that the dominant bacteria in the root canals with chronic apical periodontitis were Streptococcus spp.